β-lactam antibiotic-induced release of lipoteichoic acid from Staphylococcus aureus leads to activation of neutrophil granulocytes - Hartung Thomas; Morath Siegfried; Ziemann Christian; Starke Andrea; Lotz Sonja; Solbach Werner; Laskay Tamás (BMC, 2006)
Abstract Background Polymorphonuclear neutrophil granulocytes (PMN) are phagocytes of the first line of antimicrobial defense. Previously we demonstrated that lipoteichoic acid (LTA) from Staphylococcus aureus (S. aureus) directly activates neutrophil granulocytes. Others have reported that exposure of S. aureus to β-lactam antibiotics leads to LTA release. In the present study we addressed the question whether exposure of S. aureus to β-lactam antibiotics or antibiotics of other groups results in the generation of PMN-stimulating activity and whether this activity can be attributed to LTA. Methods S. aureus were exposed to flucloxacillin, a β-lactam antibiotic or to the protein synthesis-inhibitors erythromycin and gentamicin, or to ciprofloxacin, a gyrase inhibitor. Supernatants of the antibiotic-treated bacteria were assayed for their LTA content and for their effect on PMN functions. Results We observed that exposure of S. aureus to flucloxacillin and, to a lesser degree to ciprofloxacin, but not to erythromycin or gentamicin led to LTA release. Co-incubation of neutrophil granulocytes with LTA-containing supernatants led to PMN activation as assed by morphological changes, release of IL-8, delay of spontaneous apoptosis and enhanced phagocytic activity. Depletion of LTA from the supernatants markedly reduced their PMN-activating capacity. Conclusion The findings suggest that, via the activation of PMN, antibiotic-induced LTA release from S. aureus leads to enhanced antimicrobial activity of the innate immune defense mechanisms.